Efeitos da amonização sobre a ocorrência de fungos, composição química e digestibilidade in vitro de fenos de grama seda (Cynodon dactylon (L.) Pers.) - Reis, Ricardo Andrade [UNESP]; De Cássia Panizzi, Rita [UNESP]; Rosa, Beneval [UNESP]; De Andrade Rodrigues, Luis Roberto [UNESP]; Nascimento, Jussimara Manoela [UNESP] (My University, 1997)
The experiment was conducted with grama seda (Cynodon dactylon (L.) Pers.) hays stored with a low moisture content (12-15%) and without chemical treatment, and hays stored with a high moisture content (20-25%) and treated with anhydrous ammonia (NH3) at 0.5 and 1.0% of DM, and urea at 0.9 and 1.8% of DM. At 65 days after treatment (AT) under a plastic cover, the bales were opened and samples were taken at 3, 15 and 30 days to determine the chemical composition and in vitro digestibility (IVDMD) of the hays. For the identification of fungi, samples were taken at 0, 15 and 30 days AT. The data were analyzed according to a split-plot design with the effects of the chemical treatments studied in the main plot and the effects of the periods of post-treatment studied in the sub-plots. Fourteen genera of fungi were observed in the hays, not treated and treated with NH3 and urea, with a higher occurrence of Cladosporium, Curvularia, Aspergillus, and Penicillium. Treatment with anhydrous ammonia and 1.8% urea controlled the occurrence of Aspergillus; however, Penicillium decreased in hays treated with ammonia 30 days AT. Ammoniation did not influence the contents of ADF, cellulose and lignin in the hays, but NDF and hemicellulose decreased with the use of ammonia 30 days AT. The CP contents and the IVDMD increased with ammoniation. The CP contents decreased in hays treated with NH3 as days AT increase, while hays treated with urea did not change.
Effects of the ammoniation on the occurrence of fungi, chemical composition, and in vitro digestibility of grama seda (Cynodon dactylon (L.) Pers) hays
Keywords: Anhydrous ammonia; Fungi; Grass hay; IVDMD; Urea